Study on the spatiotemporal evolution of vegetation and the spatial heterogeneity of its influencing factors based on land use policy zoning in Anhui Province: providing new ideas for vegetation protection - Zhu, Xinyi; Dong, Bin (Frontiers in Environmental Science, 2025)
Identifying the primary factors influencing changes in vegetation cover within different land use policy zones, along with their spatial heterogeneity and the spatiotemporal evolution characteristics of past and future vegetation cover, is essential for effective Fractional Vegetation Cover (FVC) management. This study utilizes a Self-Organizing Feature Map (SOFM) neural network to identify land use policy zones in Anhui Province. By coupling the SEN+MK trend test with the Hurst index, the study predicts future vegetation change trends. A multiscale geographically weighted regression model is employed to reveal the spatial heterogeneity of the influencing factors of FVC, and a geographical detector is used to analyze the main influencing factors in different land use policy zones. The results indicate the following: From 2000 to 2023, the FVC in Anhui Province predominantly ranged between 0.4 and 0.6. Over these 24 years, the highest average FVC was found in the core ecological protection zone. The areas with the most significant improvement and fluctuation were located in the core agricultural production zone. Future improvements and degradations are primarily concentrated in the core agricultural production zone. The main driving factors differ across various land use policy zones. Climate factors dominate in Anhui Province as a whole, the core agricultural production zone, and the ecological protection transition zone. Topographical factors are predominant in the core ecological protection zone, whereas socioeconomic factors are the primary drivers in the core economic development zone. This study provides theoretical guidance for optimizing vegetation protection policies, coordinating human-environment relationships, and achieving sustainable development across different policy zones.